2013
DOI: 10.1248/bpb.b12-01032
|View full text |Cite
|
Sign up to set email alerts
|

The Polymerization Agent, 2-Methyl-4′-(methylthio)-2-morpholinopropiophenone Induces Caspases-3/7 in Human Blood Mononuclear Cells <i>in Vitro</i>

Abstract: Our previous studies detected the presence of a photoinitiator 2-methyl-4′-(methylthio)-2-morpholinopropiophenone (MTMP) in an intravenous (i.v.) injection bag solution. Importantly, MTMP has demonstrated cytotoxicity for normal human peripheral blood (PB) mononuclear cells (MNC). Cell death pathways have two well-known modes, apoptosis and necrosis. But it has not been clear whether MTMP induced apoptosis or necrosis in normal human PB MNC. In the present in vitro study, we examined normal human PB MNC for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…28 A follow-up study found cytotoxicity of PI-907 for human peripheral blood mononuclear cells. 29 2-Benzyl-2-(dimethylamino)-4′-morpholinobutyrophenone (PI-369), which has a similar structure to PI-907, was detected at much lower concentrations (<MQL− 879 pg/mL; GM: 1.68 pg/mL) and frequency (8%). The possible reasons of lower detection of PI-369 (lgK ow = 4.50) in the serum samples might include its limited use and/or higher predicted hydrophobicity compared to PI-907 (logK ow = 2.73) (Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 A follow-up study found cytotoxicity of PI-907 for human peripheral blood mononuclear cells. 29 2-Benzyl-2-(dimethylamino)-4′-morpholinobutyrophenone (PI-369), which has a similar structure to PI-907, was detected at much lower concentrations (<MQL− 879 pg/mL; GM: 1.68 pg/mL) and frequency (8%). The possible reasons of lower detection of PI-369 (lgK ow = 4.50) in the serum samples might include its limited use and/or higher predicted hydrophobicity compared to PI-907 (logK ow = 2.73) (Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One previously identified exposure pathway of PI-907 was via intravenous injection bag solutions . A follow-up study found cytotoxicity of PI-907 for human peripheral blood mononuclear cells . 2-Benzyl-2-(dimethylamino)-4′-morpholinobutyrophenone (PI-369), which has a similar structure to PI-907, was detected at much lower concentrations (<MQL–879 pg/mL; GM: 1.68 pg/mL) and frequency (8%).…”
Section: Resultsmentioning
confidence: 99%
“…This activity caused by EHDAB was also observed in human estrogen receptor α (hERα) and hERβ stably transfected HEK293 cells . However, an in vivo study based on uterotrophic assay and transgenic zebrafish assay did not detect the estrogenic activity of EHDAB. , Conversely, PI-907 can induce apoptosis of human peripheral blood mononuclear cells by activating caspases-3/7 . Exposure to PI-907 considerably reduced cell viability according to the MTT assay .…”
Section: Toxicitymentioning
confidence: 94%
“…126,127 Conversely, PI-907 can induce apoptosis of human peripheral blood mononuclear cells by activating caspases-3/7. 128 Exposure to PI-907 considerably reduced cell viability according to the MTT assay. 73 Additionally, DEAB exposure substantially increased the percentage of slightly damaged HL-60 cells, as measured by the comet assay and trypan blue dye exclusion, indicating its DNA-damaging activity.…”
Section: Toxicitymentioning
confidence: 98%
“…However, the pharmacokinetics of MTMP have yet to be elucidated in detail. We showed that MTMP induced apoptosis through a caspase-dependent pathway via caspase-3/7 in vitro ( Kawasaki et al, 2013 ). Moreover, 1-HCHPK, MBB, and MTMP did not exhibit mutagenicity in the Ames test.…”
Section: Introductionmentioning
confidence: 99%